2014
DOI: 10.1080/15564886.2014.939798
|View full text |Cite
|
Sign up to set email alerts
|

Police Sexual Misconduct: Arrested Officers and Their Victims

Abstract: Police sexual misconduct encompasses a range of acts from less serious noncriminal behaviors to more egregious criminal behaviors including police sexual violence. Victims of sex crimes are often reluctant to report sexual abuse when the offender is a police officer. The study provides empirical data on 771 sex-related arrest cases from 2005 to 2008 of 555 sworn officers at 449 nonfederal law enforcement agencies across the United States. The study identifies and describes incidents where officers were arreste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…We also found that courts were more likely to convict an officer of a profit-motivated crime in cases where the officer had lost his or her job after being arrested. Prior research has shown that police officers are likely to be convicted in cases where they lost their jobs after being charged with serious crimes involving acts of police sexual violence (Stinson, Brewer, Mathna, Liederbach, & Englebrecht, 2014). Officers are unlikely to be convicted or lose their job, however, when charged with less serious crimes such as drunk driving or incidents involving acts of officerinvolved domestic violence Stinson, Liederbach, Brewer, & Todak, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that courts were more likely to convict an officer of a profit-motivated crime in cases where the officer had lost his or her job after being arrested. Prior research has shown that police officers are likely to be convicted in cases where they lost their jobs after being charged with serious crimes involving acts of police sexual violence (Stinson, Brewer, Mathna, Liederbach, & Englebrecht, 2014). Officers are unlikely to be convicted or lose their job, however, when charged with less serious crimes such as drunk driving or incidents involving acts of officerinvolved domestic violence Stinson, Liederbach, Brewer, & Todak, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…First, although grand juries typically comply with indictment requests (17), police officers are rarely indicted for severe actions, such as police shootings (18). Between 2005 and 2011, 41 officers were charged with manslaughter or murder in connection with on-duty shootings; during the same period, about 2,700 justified homicides by police were reported to the Federal Bureau of Investigation (19). Second, participants made decisions individually (rather than in groups, as do real grand jurors).…”
Section: Methodsmentioning
confidence: 99%
“…For men and Trans people, reporting rates of rape are lower and greatly undercounted in prison records (Robertson, 2003). Similar trends are found in the documented arrests of police officers in the U.S. Of the 545 cases of arrests of police officers for sex-related crimes between 2005 to 2007, over half (51.3%) were arrested for sexual misconduct on duty or when acting in an official capacity, 32.2% for forcible or statutory rape, 19.5% for forcible fondling and 10% statutory rape (Stinson et al, 2015).…”
Section: Introductionmentioning
confidence: 54%